Unisphere completed
Caption, "Ready and WaitingThe Unisphere structure, completed by United States Steel well ahead of the opening date for New York World's Fair - (April 22nd) - awaits testing of fountains that will encircle Unisphere base with cascading water. Shown left and right are lighting towers to be used in illuminating the largest stainless steel structure in the world."